Daily garden use and quality of life in persons with advanced dementia living in a nursing home: A feasibility study - Melanie van derVelde‐van Buuringen; Wilco P. Achterberg; Monique A.A. Caljouw (Wiley, 2021)
Abstract Aim To evaluate the process of daily going outside in a nursing home garden and explore the effect of garden use on quality of life and neuropsychiatric symptoms in persons with dementia. Design A feasibility study with quantitative and qualitative approaches. Methods Twenty residents with a diagnosis of moderate‐to‐severe dementia participated. The intervention consisted of at least 30 min of garden use, whereby any activity outside is possible as long as it is person‐centred and fitting within usual daily nursing home practice. Interviews were held with caregivers, and questionnaires were sent to other disciplines involved. Quality of life (QUALIDEM) and neuropsychiatric symptoms (NPI‐NH) were collected at baseline, intervention and postintervention. Results Caregivers experienced and observed benefits of going outside for themselves, in residents and relatives. Incorporating daily garden use does not imply an additional task, but rather rearranging priorities and doing the usual activities outside a part of the time.